2008
DOI: 10.1152/ajprenal.00618.2007
|View full text |Cite
|
Sign up to set email alerts
|

VEGF receptors and neuropilins are expressed in the urothelial and neuronal cells in normal mouse urinary bladder and are upregulated in inflammation

Abstract: RE, Saban R. VEGF receptors and neuropilins are expressed in the urothelial and neuronal cells in normal mouse urinary bladder and are upregulated in inflammation. Am J Physiol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
70
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 37 publications
7
70
1
Order By: Relevance
“…Recent studies have suggested that the VEGF-VEGF receptor system may participate in the pathogenesis of IC/painful bladder syndrome (7,49,52) and other inflammatory conditions, including IBD (11,15,23,33). Intravesical corticotropinreleasing hormone and acute restraint stress induce mast celldependent VEGF release from bladder explants (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that the VEGF-VEGF receptor system may participate in the pathogenesis of IC/painful bladder syndrome (7,49,52) and other inflammatory conditions, including IBD (11,15,23,33). Intravesical corticotropinreleasing hormone and acute restraint stress induce mast celldependent VEGF release from bladder explants (7).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated upregulation of VEGFR-1 in urinary bladder after LPS-induced bladder inflammation in the mouse (50). More recent studies have demonstrated the presence, accessibility, and functionality of VEGFR-1, VEGFR-2, and Npns in urothelial cells from control and inflamed mouse bladder (49). Although VEGF has been implicated in the pathogenesis of IBD (15,23,33), less is known about the potential contribution of VEGF to IC/painful bladder syndrome.…”
mentioning
confidence: 99%
“…[21][22][23] Based on data obtained in a previous observational clinical study in bladder cancer patients receiving intravesical BCG therapy as well as published experimental data, we concluded that multiple BCG treatments resulted in a "prime/boost" response for the innate immune system. 21,24,25 Intermittent intravesical therapy resulted in tissue remodeling with increased vascularization, thus accounting for a 200-fold increase in neutrophils influx, a 120-fold increase in inflammatory monocytes and a 30-fold increase in natural killer cells. 21 Using quantitative data from this study as well as our knowledge of the kinetics of bladder tumor growth, we reasoned that it would be possible to establish a mathematical model that could help test the prediction that the innate immune response accounts for the success of bladder cancer immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…This assumption is supported by the observation that migration of effector cells is linked to the vascularization of the bladder wall, which evolves as a function of inflammation induced cell death. 21,25 As such, the increase in the inflow of immune cells depends on the number of BCG-associated cells present in the bladder, which are triggers for activation and effector activity of innate immune cells.…”
Section: Assumption 3: Bcg Instillations Results In An Increased Recrumentioning
confidence: 99%
See 1 more Smart Citation